Pengaruh Kepatuhan Wajib Pajak Orang Pribadi Berdasarkan Theory Planned Of Behaviour (TPB) - Hurian Kamela (Pusat P2M Politeknik Negeri Batam, 2020)
There must be an awareness of the public regarding compliance in paying taxes. Tax is a state asset that is collected by the state for the common interest. The role of society in paying taxes must be accompanied by internal (within) the individual itself because there are still limited people who know that taxes are crucial. This study aims to link the effect of individual taxpayer compliance based on the